2007
DOI: 10.1038/sj.hdy.6800962
|View full text |Cite
|
Sign up to set email alerts
|

Mating patterns and contemporary gene flow by pollen in a large continuous and a small isolated population of the scattered forest tree Sorbus torminalis

Abstract: The influence of population size and spatial isolation on contemporary gene flow by pollen and mating patterns in temperate forest trees are not well documented, although they are crucial factors in the life history of plant species. We analysed a small, isolated population and a large, continuous population of the insect-pollinated tree species Sorbus torminalis in two consecutive years. The species recently experienced increased habitat fragmentation due to altered forest management leading to forests with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 41 publications
3
49
1
1
Order By: Relevance
“…1999; Hoebee et al. 2007; Duminil et al. 2009), but in H. oldfieldii outcrossing rates did not differ significantly among populations of different size, shape, or plant density.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1999; Hoebee et al. 2007; Duminil et al. 2009), but in H. oldfieldii outcrossing rates did not differ significantly among populations of different size, shape, or plant density.…”
Section: Discussionmentioning
confidence: 99%
“…The nearest population was over 1 km away and therefore this provides evidence for some pollen dispersal between populations across different habitat at a level similar to those found in other woody species with disjunct populations (Robledo‐Arnuncio and Gill 2005; Hoebee et al. 2007; Sampson et al. 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacles et al (2004) suggested that low pollen dispersal arose from localized foraging of pollinators and infrequent travel between remnant populations at their windy site. The effect of isolation on pollen immigration was further highlighted in a study of two Sorbus torminalis woods, one of which was part of a continuous large population and the other a small more-isolated population (Hoebee et al, 2007). In the continuous population, immigrant pollination accounted for 36-39% of paternity compared with only 8% in the isolated population.…”
Section: Discussionmentioning
confidence: 99%